169Yb‐based rotating shield brachytherapy for prostate cancer. Issue 12 (1st November 2020) - Adams, Quentin; Hopfensperger, Karolyn M.; Kim, Yusung; Wu, Xiaodong; Flynn, Ryan T.
Abstract : Purpose: To present a system for the treatment of prostate cancer in a single‐fraction regimen using 169 Yb‐based rotating shield brachytherapy (RSBT) with a single‐catheter robotic delivery system. The proposed system is innovative because it can deliver RSBT through multiple implanted needles independently, in serial, using flexible catheters, with no inter‐needle shielding effects and without the need to rotate multiple shielded catheters inside the needles simultaneously, resulting in a simple, mechanically robust, delivery approach. RSBT was compared to conventional 192 Ir‐based high‐dose‐rate brachytherapy (HDR‐BT) in a treatment planning study with dose escalation and urethral sparing goals, representing single‐fraction brachytherapy monotherapy and brachytherapy as a boost to external beam radiotherapy, respectively. A prototype mechanical delivery system was constructed and quantitatively evaluated as a proof of concept. Methods: Treatment plans for twenty‐six patients with single fraction prescriptions of 20.5 and 15 Gy, were created for dose escalation and urethral sparing, respectively. The RSBT and HDR‐BT delivery systems were modeled with one partially shielded 999 GBq (27 Ci) 169 Yb source and one 370 GBq (10 Ci) 192 Ir source, respectively. A prototype angular drive system for helical source delivery was constructed. Mechanical accuracy measurements of source translational position and angular orientation in a simulated treatment delivery setup were obtained using the prototype system. Results: For dose escalation, with equivalent urethra D 10%, PTV D 90% for RSBT vs HDR‐BT increased from 22.6 ± 0.0 Gy (average ± standard deviation) to 29.3 ± 0.9 Gy, or 29.9 % ± 3.0%, with treatment times of 51.4 ± 6.1 min for RSBT and 15.8 ± 2.3 min for 10 Ci 192 Ir‐based HDR‐BT. For urethra sparing, with equivalent PTV D90 %, urethra D 10% for RSBT vs HDR‐BT decreased for RSBT vs HDR‐BT from 15.6 ± 0.4 Gy to 12.0 ± 0.4 Gy, or 23.1% ± 3.5%, with treatment times of 30.0 ± 3.7 min for RSBT and 12.3 ± 1.8 min for HDR‐BT. Differences between measured vs predicted rotating catheter positions (corresponding to source position) were within 0.18 mm ± 0.12 mm longitudinally and 0.07° ± 0.78°. Conclusion: 169 Yb‐based RSBT can increase PTV D 90% or decrease urethral D 10% relative to HDR‐BT with treatment times of less than 1 h using a single‐source robotic delivery system with treatment delivered in a single fraction. The prototype helical delivery system was able to demonstrate adequate mechanical accuracy.